2018
DOI: 10.3390/nu10020118
|View full text |Cite
|
Sign up to set email alerts
|

What Constitutes Traditional and Modern Eating? The Case of Japan

Abstract: Traditional Japanese dietary culture might be a factor contributing to the high life expectancy in Japan. As little is known about what constitutes traditional and modern eating in Japan, the aims of the current study were to (1) comprehensively compile and systematize the various facets of traditional and modern eating; and (2) investigate whether these facets also apply to traditional and modern eating in Japan. In Study 1, an extensive international literature review was performed. Forty-five facets of trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Furthermore, the TEP10 framework enables researchers to uncover similarities and differences in the concept of traditional and modern eating across the world. In the case of Japan, we have already investigated whether the presented multidimensionality of traditional and modern eating is valid [64]. Specifically, we asked 340 adults from Japan to rate the ‘traditionality’ of 46 facets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the TEP10 framework enables researchers to uncover similarities and differences in the concept of traditional and modern eating across the world. In the case of Japan, we have already investigated whether the presented multidimensionality of traditional and modern eating is valid [64]. Specifically, we asked 340 adults from Japan to rate the ‘traditionality’ of 46 facets.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that, in accordance with the TEP10 framework, traditional and modern eating is also multidimensional in Japan. More precisely, both dimensions what and how people eat are part of traditional and modern eating in Japan as well as ten subdimensions of the TEP10 framework [64].…”
Section: Discussionmentioning
confidence: 99%
“…Japan has the highest average life expectancy at birth in the world (40) . The main contributor to this is thought to be the traditional Japanese dietary patterns (5) , which are characterized by eating dishes and meals with fish, soyabean products, rice and other grains, and vegetables cooked using traditional methods (41,42) , as well as eating at mealtimes, at home and with other people (43) . Although the traditional Japanese diet may be associated with lower risk of diseases (5) , the consumption of ultra-processed foods among the Japanese population, and their effects on diet quality and health, have not been clarified yet.…”
mentioning
confidence: 99%
“…With the advance of global urbanization and the Westernization of lifestyles, the dietary patterns of industrialized countries appear to be increasingly converging toward a Western diet 33) . This trend is very obvious in Japan, and has undergone a dramatic transformation in which the rice-based diet prevalent for over 2000 years is being replaced by a wheat-based diet centered around bread and pasta 34,35) . Meat consumption also rose from approximately 300 g/person/year in the 1910s to approximately 5.2 kg/person/year in the 1960s, and this amount has since only continued to increase 36) .…”
Section: Discussionmentioning
confidence: 99%